Efficient Production of High-Quality Infrared-Assisted Spouted Bed-Dried Areca taro Based on the Drying Temperature and Cutting Size Control - Yitong Zhao; Fanqianhui Yu (Foods, 2024)
The purpose of this study was to apply infrared-assisted spouted bed drying (IRSBD) technology for Areca taro drying and to investigate the effects of different parameters on its drying quality. Specifically, in order to determine the suitable conditions for IRSBD, the effects of different drying temperatures (45 °C, 50 °C, 55 °C, and 60 °C) and cutting sizes (6 × 6 × 6 mm, 8 × 8 × 8 mm, 10 × 10 × 10 mm, and 12 × 12 × 12 mm) on the drying characteristics, temperature uniformity, and quality properties (including colour, rehydration ratio, total phenol content, total flavonoid content, and antioxidant activity) of Areca taro were studied. The results showed that the optimal drying condition was the sample with a cutting size of 10 × 10 × 10 mm and drying at 50 °C, which yielded the dried sample with the best colour, highest total phenol and flavonoid contents, maximum antioxidant capacity, and rehydration ratio.